Suriname : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report, 2012)
The economy continues to recover at a steady pace, buoyed by strong activity in the oil and gold sectors, as well as public investment. In the wake of the January 2011 devaluation and concurrent increase in taxes, the fiscal balance shifted from a deficit of 3 percent of GDP in 2010 to a surplus of 1 percent in 2011. The balance of payment also strengthened significantly, boosting reserves to nearly USD 1 billion (5u months of imports) at end-2011. With still-tight monetary conditions, 12-month inflation dropped to 3.6 percent in May 2012, from a peak of over 22 percent in April 2011.